2012
DOI: 10.1080/00028487.2012.675905
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Seasonal Habitat Use and Diel Vertical Activity of Lake Whitefish in Clear Lake, Maine, as Determined with Acoustic Telemetry

Abstract: Seasonal and daily vertical activity of lake whitefish Coregonus clupeaformis was studied in Clear Lake, Maine (253 ha), using acoustic telemetry from November 2004 to June 2009. Twenty adult lake whitefish were tagged with acoustic tags that had either a depth sensor or both depth and temperature sensors to assess vertical habitat use at a seasonal and daily resolution. Vertical habitat selection varied seasonally and was strongly influenced by temperature. Between December and April, when the lake was covere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…The two species differ in their reported preferred temperature ranges and presumably use different habitats in lakes. Lake whitefish have a consistent preferred thermal range in lakes (10-14°C; Christie & Regier, 1988;10-15°C;Gorsky, Zydlewski, & Basley, 2012), which should place lake whitefish habitat at or just below the summer thermocline depth. No additional research appears to have been conducted addressing the utility of the thermal habitat envelope defined by Christie and Regier (1988).…”
Section: Introductionmentioning
confidence: 99%
“…The two species differ in their reported preferred temperature ranges and presumably use different habitats in lakes. Lake whitefish have a consistent preferred thermal range in lakes (10-14°C; Christie & Regier, 1988;10-15°C;Gorsky, Zydlewski, & Basley, 2012), which should place lake whitefish habitat at or just below the summer thermocline depth. No additional research appears to have been conducted addressing the utility of the thermal habitat envelope defined by Christie and Regier (1988).…”
Section: Introductionmentioning
confidence: 99%
“…Transmitters and data loggers can provide data on the horizontal movements of animals, and also their depth distributions and vertical movements, yielding many insights into their behavior. Analysis of vertical movement data may reveal that a species' depth distribution is influenced by factors including temperature [1,2], oxygen [3], the former two in concert [4], light level [5,6], predation risk [7], prey movements [8,9], and foraging efficiency [10,11]. Consequently, vertical distributions often vary with the seasons and diel periods [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…These are conditions that dwarf fish may experience while foraging in the warmer limnetic zone in the summer (Gorsky et al. ; Evans et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, found that dwarf fish have more cathodic hemoglobins, which aid in oxygen uptake during hypoxia, at high temperatures (which can induce hypoxia), and with metabolic acidosis (Mairbãurl and Weber 2012). These are conditions that dwarf fish may experience while foraging in the warmer limnetic zone in the summer (Gorsky et al 2012;Evans et al 2014). Together, these data hint that differences in oxygen transport cascade-related traits in Lake Whitefish ecotypes may be the product of multiple interacting selective pressures, including activity levels, environmental oxygen content, and temperature.…”
Section: Ecotypesmentioning
confidence: 99%